2018
DOI: 10.4491/eer.2018.193
|View full text |Cite
|
Sign up to set email alerts
|

Advances in microalgal biomass/bioenergy production with agricultural by-products: Analysis with various growth rate models

Abstract: Mass cultivation of microalgae is necessary to achieve economically feasible production of microalgal biodiesel. However, the high cost of nutrients is a major limitation. In this study, corncob extract (CCE) was used as an inorganic and organic nutrient source for the mass cultivation of Chlorella vulgaris (C. vulgaris). Chemical composition analysis of CCE revealed that it contained sufficient nutrients for mixotrophic cultivation of C. vulgaris. The highest specific grow rate of C. vulgaris was obtained at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Saccharide and acetate are generally used as carbon sources for microalgae cultivation. Among them, the most commonly used carbon source is carbohydrate in the form of glucose [19]. However, the high cost of glucose leads to an infective and inefficient way to conduct.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saccharide and acetate are generally used as carbon sources for microalgae cultivation. Among them, the most commonly used carbon source is carbohydrate in the form of glucose [19]. However, the high cost of glucose leads to an infective and inefficient way to conduct.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies also have reported the increasing in microalgae biomass by mixotrophic and utilization of glycerol during cultivation as followed: Chlorella vulgaris in real centrate wastewater [9], Chlorella in dairy wastes [20], C. protothecoides in dairy wastes [11,12], Chlorella sp. in palm oil mill effluent [21], Phaeodactylum tricornitum and Chlorella vulgaris with glycerol addition as carbon source [19,22]. However, the study of cultivating microalgae in VCO mill effluent has not been further probed with the addition of glucose:glycerol at various concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to induce the formation of higher metabolite production such as pigments, and lipid production, manipulation of carbon source, and light intensity were commonly used 5 7 . Carbon sources like glucose, glycerol, or acetate have contributed to increased biomass, and lipid productivity of microalgae 11 , 12 . Light intensity also influences microalgal growth, and the biochemical composition of cells through the process of photo-acclimation, and photo-adaptation 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…or acetate have contributed to increased biomass, and lipid productivity of microalgae 11,12 . Light intensity also influences microalgal growth, and the biochemical composition of cells through the process of photo-acclimation, and photo-adaptation 13,14 .…”
mentioning
confidence: 99%